Peningkatan Keterampilan Berbicara Siswa Melalui Strategi Peer Lessons Dalam Pembelajaran Bahasa Indonesia di Kelas IV Sekolah Dasar - Magdalena Kaunang; Risal M. Merentek (Peneliti.net, 2023)
The purpose of this study is to improve speaking skills using Peer Lessons Learning Strategies for students in grade IV of GMIM Pineleng Elementary School. The research method used is the Kemis and Mc.Taggart model classroom action research. The research was carried out in 2 cycles and each cycle consisted of 4 stages, namely: planning, implementation, observation and reflection. The data collection technique in this study was through tests carried out by asking questions in writing to all students, using Student Worksheets and Assessment Sheets. The data analysis technique obtained from the teaching and learning process is characterized by an increase in Indonesian language learning outcomes, namely 75% and is calculated using the Minimum Completeness Criteria formula. The results showed that student learning outcomes using Peer Lessons learning strategies in Indonesian subjects. Before the action was taken, only 12 students or (40%) were completed, while 18 students or (60%) were still incomplete. After the first cycle of action, 20 students (66%) achieved completeness and 10 students (34%). After the second cycle of action, 26 students (84%) had completed and 4 (14%). In conclusion, the Peer Lessons Learning Strategy can improve students' speaking skills in Indonesian language class IV at GMIM Pineleng Elementary School.